Effect of Strategic Management on Job Satisfaction Among Selected Local Government Workers in Ibadan, Oyo State, Nigeria - Olawale E. Olaniyan; Funmilola E. Akinyooye; Waliyi O. Aransi; Emeka E. Okafor (Journal of Arts, Humanities and Social Science)
The study explored the effect of strategic management on job satisfaction among selected local government workers in Ibadan, Oyo State, Nigeria. A mixed-method design was employed, while three-hundred and seventy and five respondents were purposively selected from questionnaire and interview schedule sessions, respectively. Short Index of Job Satisfaction (SIJS) and Balanced Scorecard Scales were adopted and a self-designed interview guide was used to obtain information from the sampled respondents. Descriptive and inferential statistical tools were used to analyse quantitative data, while qualitative data were thematically analysed. Findings revealed that current strategic management practices among local government workers were moderately adopted, with 66.8% of respondents reporting moderate levels, while only 20.8% indicated high adoption. The prevailing job satisfaction levels showed that 50.8% of respondents felt satisfied with their jobs, and 53.5% agreed they were fairly compensated, although resource inadequacies and limited procedural efficiency were highlighted. Strategic management positively impacted service delivery satisfaction, with 56.8% of respondents affirming fair job satisfaction evaluations and 63.5% agreeing they could balance work and personal life. Barriers to implementing strategic management included political interference, cited by qualitative participants as disrupting autonomy, resistance to change (noted by 27.6% of respondents as neutral about departmental commitment to change), and inadequate technological infrastructure. The study concluded that there is a need to underscore the importance of aligning strategic management objectives with organizational goals to ensure sustainable development within the organisation. The study recommended that the concerned stakeholders should institute leadership training tailored to strategic management, enhanced financial autonomy to address resource gaps, and investments in technology to improve operational efficiency among others. This is because doing these would be essential to foster job satisfaction and enhance service delivery at the organizational level and beyond.